IoT based health monitoring system for pregnant women & children - Ohana, Fariha Islam; Rahmina, Nabita; Ahmed, Farin; Basak, Anindita (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.